Analisis Indeks Pencemaran Sungai Ampel Desa Sletreng Kabupaten Situbondo - Anita Diah Pahlewi (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
The Ampel River is one of the rivers located in Landangan Village, Kapongan District, Situbondo Regency. This river is used by the community to irrigate rice fields, fishing, and so on. The existence of PT. Panca Mitra Multiperdana Tbk. namely producers of processed shrimp around the river have an impact on the quality of the river water. This study aims to analyze the water quality in the Ampel River. The analysis was carried out using the river pollution index method based on the Decree of the Minister of the Environment of the Republic of Indonesia number 115 of 2003. The Ampel River as the research area is drained by a sewage pipe from processed shrimp and is close to local shrimp ponds. Data were collected in situ using 150 ml dark glass bottles and 600 ml clear bottles, stored in a coolbox. The research location is divided into 3 sampling point locations. The results showed that the analysis used the pollution index in the Ampel River, namely at Station I of 2.59, station II of 4.29, and station III of 4.52 where all three were categorized as lightly polluted.